Penjiplakan Lagu Nasional Indonesia oleh Warga Negara Lain (Hasanuddin Civil and Bussiness Law Review, 2026)
National songs in Indonesia play a significant role in fostering nationalism and preserving culture, one of which is the song "Halo-Halo Bandung," created by Ismail Marzuki and protected by Intellectual Property Rights (IPR). However, this song faced copyright infringement when it was modified into "Hello Kuala Lumpur" without permission. This case highlights the importance of respecting copyright. This study examines the legal protection of the song "Halo-Halo Bandung" and emphasizes the importance of honoring copyright to maintain the integrity of artistic works. This study aims to analyze legal protection for creators of copyright infringement of national songs by other countries, and analyze the legal consequences of copyright infringement by other countries. This research uses normative research methods with statutory and comparative approaches. The results of the study that the song “Halo-Halo Bandung” get legal protection in Malaysia, there are differences in the term of copyright protection between Indonesia and Malaysia. Therefore, when referring to the Bern Convention as lex specialis in the protection of copyright law across countries then Indonesia has no legal basis to take steps to protect its rights in Malaysia. The legal consequences of cross-border copyright infringement can be resolved through civil and criminal channels. In addition, YouTube as a digital platform can be held liable in accordance with the Constitutional Court Decision No. 84/PUU-XXI/2023 which amended Article 10 of the Copyright Act for allowing copyright infringement on its platform
Keywords: copyrights; national song; plagiarism; moral rights; economic rights